Analysis of Risk Factors Associated With Poor Outcome in Posterior Reversible Encephalopathy Syndrome After Treatment in Children: Systematic Review and Meta-Analysis - Hun, Marady; Tian, Jidong; Xie, Min; She, Zhou; Abdirahman, Amin Sheikh; Han, Phanna; Wan, Wuqing; Wen, Chuan (Frontiers in Neurology, 2020)
Objective Chemotherapy and hematopoietic stem cell transplantation (HSCT) play important roles in clinical etiology, symptoms, signs, imaging findings, and biochemical parameters for inducing posterior reversible encephalopathy syndrome (PRES) in pediatric oncologic diseases. We aimed to evaluate various risk factors of pediatric oncologic diseases after conducting chemotherapy and HSCT to induce PRES for predicting the clinical prognosis frequency. Methods The literature was performed on PubMed, Web of Science, and Embase databases to recognize the qualified studies. The odds ratios (ORs) of related risk factors and their corresponding 95% confidence intervals (CIs) were used to compute the pooled assessments of the outcomes. Results Six studies were included in the meta-analysis, involving 828 records. The risk of female children has a significantly higher incidence than male children in oncologic age groups of PRES. Children over the age of 10 years old in oncologic age groups develop a significantly increased risk of PRES. Acute graft-versus-host disease (GVHD) has a significant promotion effect on the occurrence of PRES. Hypertension can promote the occurrence of PRES in children. The risk of PRES in immunodeficient children increases significantly. Children with sickle cell disease (SCD) have a significantly increased risk of PRES. The risk of PRES in children with T-cell leukemia rises considerably. The central nervous system (CNS) leukemia/involvement has a significant role in promoting the occurrence of PRES in children.The pooled OR for the factors male, ≥10 years old of age, acute GVHD, hypertension, immunodeficiency, SCD, T-cell leukemia, CNS leukemia/involvement was 0.66 (95% CI: 0.58, 0.76; P<0.00001), 2.06 (95% CI: 1.23, 3.43; P<0.006), 1.32 (95% CI: 1.14, 1.53; P<0.0003), 8.84 (95% CI: 7.57, 10.32; P<0.00001), 2.72 (95% CI: 1.81, 4.08; P<0.00001), 2.87 (95% CI: 2.15, 3.83; P<0.00001), 2.84 (95% CI: 1.65, 4.88; P<0.0002), and 3.13 (95% CI: 1.43, 6.84; P<0.004), respectively. Conclusions The result of this meta-analysis suggests that female children, age over 10 years old, acute GVHD, hypertension, immunodeficiency, SCD, T-cell leukemia, and CNS leukemia/involvement are likely to have the poor outcome in pediatric oncologic/hematologic diseases in PRES.